The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/s22010080
|View full text |Cite
|
Sign up to set email alerts
|

Feature-Based Sentimental Analysis on Public Attention towards COVID-19 Using CUDA-SADBM Classification Model

Abstract: The COVID-19 pandemic has spread to almost all countries of the World and affected people both mentally and economically. The primary motivation of this research is to construct a model that takes reviews or evaluations from several people who are affected with COVID-19. As the number of cases has accelerated day by day, people are becoming panicked and concerned about their health. A good model may be helpful to provide accurate statistics in interpreting the actual records about the pandemic. In the proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This study applies four evaluation metrics as the measurement standards of this experiment to evaluate the performance of the artificial neural network model, including accuracy rate, precision rate, recall rate, and F-score [ 38 , 39 , 40 ]. True positive ( TP ) means that the predicted sentiment and the actual sentiment are both positive.…”
Section: Experiments Validation and Resultsmentioning
confidence: 99%
“…This study applies four evaluation metrics as the measurement standards of this experiment to evaluate the performance of the artificial neural network model, including accuracy rate, precision rate, recall rate, and F-score [ 38 , 39 , 40 ]. True positive ( TP ) means that the predicted sentiment and the actual sentiment are both positive.…”
Section: Experiments Validation and Resultsmentioning
confidence: 99%
“…Another study has indicated that many people have difficulty distinguishing between fake news and real news, irrespective of their gender, age, or educational attainment [ 10 ]. Social media platforms have presented a virtual environment for posting [ 11 ], discussion, exchange of views, and global interaction among users [ 12 ], without restrictions on location, time, or content volume [ 13 ]. A survey conducted in 2017 claimed that 67% of people in the US got their news mainly from social media [ 14 ].…”
Section: Introductionmentioning
confidence: 99%